Comparison of the Effectiveness and Safety of Transvesical Open Prostatectomy versus Transurethral Resection of the Prostate in Patients with Benign Prostatic Hyperplasia with a Prostate Weight of 65-40 Gram - Sofimajidpour , Heshmatollah; Khoshyar , Aida; Zareie , Bushra; Sofimajidpour , Hooshmand; Rasouli, Mohammad Aziz (Urology Journal, 2020)
Purpose: The aim of this study was to evaluate the efficacy of transvesical open prostatectomy (OP) compared with transurethral resection of the prostate (TURP) in patients with benign prostate hyperplasia (BPH) with a prostate weight of 40-65 grams. The short-term and long-term complications of these two procedures were also assessed. Materials and Methods: In this retrospective study, we included 160 consecutive patients with BPH who had undergone TURP (n=80) or OP surgery (n=80) from 2006 to 2017. Inclusion criteria were positive history of BPH, definite indication for prostatectomy, and prostate weight between 40 to 65 grams. Patients were evaluated for duration of hospitalization, need for re-operation, short-term and long-term postoperative complications, urinary flow rate, peak flow rate (Q max) and international prostate symptom score (IPSS). Results: The mean age ± Standard Deviation (SD) of patients’ age was 62.4 ± 3.7 and 67.2 ± 4.6 years in the TURP and OP groups, respectively. Four (5%) and seven (8.7%) patients required transfusion in the TURP group and OP groups, respectively. Dysuria was significantly more frequent in the TURP group from week two to 12 months after surgery as compared with the OP group (P < .001). Hemodynamic changes and decrease in serum sodium level were not reported in either group. However, the urinary retention and need for urinary catheterization in the first year was significantly different between the two groups with 10 cases (12.5%) in the TURP group and no cases in the OP group (P<0.001). The need for reoperation in the TURP group was reported (27 procedures on 19 patients) (33.7%) of patients. Furthermore, retrograde ejaculation (RE) was reported in 65 (81.2%) and 80 patients (100%) of the TURP and OP group, respectively. Conclusion: Despite the fact that TURP is the standard method of treatment for BPH when the prostate weighs between 40-65 grams, the results of our study showed that OP is a more efficient and safe surgery for these patients and is associated with less complications. Furthermore, the need for re-operation seems to be higher in patients with TURP.